Pendayagunaan Kohesi Sosial Petani Perempuan Single Parent di Kabupaten Muna Barat - Mursin, Mursin; Nurwiati, Nurwiati; Vadly Sanduan, Varis; Sama, Abinus; Al-Islam Asrul, Taufiq; Mitra, Robi (LP3M, Universitas Muhammadiyah Kendari, 2025)
This study aims to explore the forms of social cohesion among single-parent female farmers in Sangia Tiworo Village, South Tiworo District, West Muna Regency, Southeast Sulawesi. Using a descriptive qualitative approach with an ethnographic method, this research focuses on how social cohesion empowers single-parent female farmers in their daily lives. The findings reveal that the solidarity built among them serves as a crucial factor in maintaining their motivation to manage agricultural land, particularly in cultivating patchouli plants (Pogostemon cablin Benth). The spirit of cooperation among patchouli farmers is evident in various stages, including land preparation, seedling, plant maintenance, and post-harvest activities. This support system encourages them to continue developing their agricultural land despite the challenges they face as single parents. In addition to solidarity, their success is also influenced by a strong work ethic. Principles such as hard work, discipline in time management, proactive engagement in farming, honesty, openness, responsibility, and a strong commitment serve as the foundation for the sustainability of their agricultural endeavors.